PENGARUH INFLASI, SUKU BUNGA, NILAI TUKAR, DAN PERTUMBUHAN EKONOMI TERHADAP IHSG - Muhammad Dhenis Aika Putra Hakim; Virna Sulfitri (STMIK Widuri Jakarta, 2023)
This study aims to provide empirical evidence regarding the effect of inflation, interest rates,exchange rates and economic growth on the IDX Composite.The data sample for this research was taken from the monthly reports of BPS and Bank Indonesia for the 2018 – 2022 period. The research sample was selected using the randomized sampling method and a total of 60 samples were obtained.This study uses multiple linear regression analysis to analyze the effect of inflation, interestrates, exchange rates and economic growth on the IDX Composite. The results of this study indicatethat inflation has no effect on the IDX Composite. Meanwhile, interest rates and exchange rates have anegative effect on the IDX Composite. And, Economic Growth has a positive effect on the IDX Composite